Characterisation of functional properties of Envelopes of highly neutralisation resistant HIV-1 isolates - Guled, Fatuma Hassan (Department of Pathology, 2019)
An effective antibody-based HIV-1 vaccine would ideally elicit potent antibodies capable of neutralising a wide range of HIV-1 isolates to better cover the human population. A primary concern is the virus’ ability to rapidly escape an antibody response. A strong neutralising response elicited by a vaccine may, in principle, select for viruses that are highly antibody resistant thereby significantly reducing the benefit of a vaccine. It is therefore important to study and better understand highly neutralisation resistant viruses. To this effect, we characterized sets of subtype C and CRF02_AG viruses whose neutralisation phenotype were well defined using within subtype neutralisation (neutralisation by subtype matched sera). Our main aim was to determine if there exists a relationship between neutralisation resistance and entry efficiency. Very highly neutralisation resistant viruses appear under-represented in the population. We hypothesised that this may be at least partially explained by decreased entry efficiency as changes to Envelope (Env) during escape could affect the entry process and provide opposing selective pressure that discourages the appearance of very highly neutralisation-resistant viruses. By comparing entry efficiencies of tier 3 viruses (highly resistant) to tier 2 (moderately resistant) and 1B (sensitive), we observed that the tier 3 viruses generally exhibited higher entry efficiency. This was the opposed of what we hypothesised at the outset of these experiments. We also measured characteristics of resistant HIV-1 Envs that can be inferred from the primary sequence such as the variable loop lengths, number of glycans and net charge. We found that the V2 net charge and the V5 loop length were associated with neutralisation resistance in subtype C viruses and the V2 loop length was associated with resistance in the CRF02_AG viruses. By analysing glycosylation patterns between the groups, we found that the presence of an N-linked glycan at position 413 and the lack of a glycan at N332 were predictors of neutralisation resistance in subtype C viruses. Tier 3 viruses were also more resistant than tier 2 and 1B viruses to the PGT121 (V3/glycan), 4E10 (MPER) and the CD4 binding site broadly neutralising antibodies VRC01 and 3BNC117; suggesting that the epitopes of these antibodies are important for driving resistance. Furthermore, we found no significant relationship between susceptibility to the entry inhibitors Maraviroc and PSC RANTES (CCR5 antagonists) and the fusion inhibitor T20 and resistance, indicating that neutralisation resistance did not alter inhibitor target sites. Based on our findings, it is clear that reduced entry efficiency does not explain why highly resistant viruses are not more common. We may speculate that the evolutionary steps needed to reach very high neutralisation resistance may be difficult to go through and/or that other countervailing selective pressures may be involved. In the context of an antibody based intervention, highly resistant viruses with increased entry efficiency circulating in the population could be a set back in the control of the HIV-1 epidemic. Therefore, for any long-term antibody-based intervention to be globally relevant it must elicit responses that limit occurrence of resistance and also increase chances that escape would lead to severely impaired viral fitness.